Green supply chain strategy in Taiwan electronic firms for WEEE and RoHs: A case study on the green practices in the electronics sector - Chou, Hsin-YI (2018)
According to the WEEE and RoHs directives executed by European union, Taiwan electrical industries should consider waste disposal and hazardous materials use in their supply chain. Taiwan electronic companies, especially in Original Equipment Manufacturer and Original Design Manufacturer in the semiconductor were seriously affected by the EU regulation if they would failed to transfer itself to the green supply chain. In addition, there are also some other barriers existed in the Taiwan electronic market negatively affecting companies performance in many aspects. Green supply chain management (GSCM) makes a company optimally allocate internal resources to provide green products. In addition, Green supply chain management (GSCM) practice and strategy are necessary used for responding WEEE and RoHs because those are the primary concepts of introducing the green supply chain.